Pencegahan Stunting Melalui Family Empowerment bagi Ibu Hamil - Mardiana, Mardiana; Oksidriyani, Safrina; Dimarti, Safira Chairani; Rokhmah, Farida Dwi; Rasyad, Ula Faza Nayli; Faizin, Miftahul; Rihadhatul, Shoofia; Bila, Syifa Salsa; Pratiwi, Salma Eka; Salma, Rania; Permata, Gracia Dara; Putri, Safna Afifa; Mumtazul, Alfi; Nur, Zakiah (Berdikari: Jurnal Inovasi dan Penerapan Ipteks, 2024)
Various factors cause stunting in children, one of which is the mother’s malnutrition during pregnancy. Mothers who have Chronic Energy Deficiency (CED) and anemia have a high potential of giving birth to children prone to stunting. This community service aims to increase the knowledge of pregnant women and increase the role of the family in preventing CED and anemia in pregnant women in the Sekaran Puskesmas area by developing a class program for pregnant women, making pocketbooks, and supporting educational media. The applied methods were assistance and counseling for pregnant women and parents, education for pregnant women and companions, anthropometry training for cadres and TPK, preparation of e-booklet media for pregnant women, and cooking demos for healthy menus for pregnant women. The results of this activity showed an increase in knowledge based on the pre-test results of pregnant women <80 by 27.3% and scores >80 by 72.7%. After carrying out the posttest, 100% of participants obtained >80 scores. This shows an increase in the incidence of CED and anemia in pregnant women. In the pre-test results for pregnant women’s companions, 10% of the results were obtained with a score of <80 and a score of >80 of 90%. After carrying out the post-test, all participants had >80 scores. Accordingly, Family Empowerment activities for pregnant women with CED and anemia can increase the knowledge of pregnant women and their companions regarding the handling and prevention of CED and anemia. Keywords: Family empowerment, Pregnant Women with Chronic Energy Deficiency, Anemia, Stunting